Gender, livestock and reducing greenhouse gas emissions in Costa Rica - Farnworth, Cathy Rozel (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Costa Rica is developing a Nationally Appropriate Mitigation Activity (NAMA) that will provide climate finance for best livestock management practices that generate climate change mitigation benefits. The LivestockPlus research project, implemented by the International Center for Tropical Agriculture (CIAT) and partners, seeks to inform the NAMA by providing scientific evidence for improved pasture and cattle management to sustainably improve yields while also reducing emissions. Women are a target beneficiary of the research, yet the relevance of gender to the project’s aims has been unclear. A scoping exercise to identify opportunities to strengthen the gender component was therefore undertaken in 2015 using a case study in Costa Rica and a literature review. This exercise identified women’s roles as (1) co-decision-makers with men in the household, (2) users of milk for making cheese (most households) and (3) farmers directly involved in livestock production activities under some circumstances. Girls, together with boys, frequently played a role in the daily care of animals, which may influence girls’ capacities and willingness to become future farmers. The scoping exercise indicated opportunities for enhancing women’s roles in the cattle value chain and more generally, supporting women’s inclusion in (i) livestock and innovation for climate change mitigation, (ii) gender-responsive implementation of the NAMA, and (iii) capacity development.